Seismic damage scenarios for Mayotte: a tool for disaster management - Taillefer, Nicolas; Bertil, Didier; Negulescu, Caterina; Roullé, Agathe; Iasio, Christian; Auclair, Samuel; Quique, Robin (Comptes Rendus. Géoscience)
A new marine volcano is erupting offshore Mayotte since May 2018, generating numerous earthquakes. The population felt many of them and the stronger shaking of the ongoing sequence caused slight damage to buildings. Historical records also confirm that damaging earthquakes had occurred in the past in this region. Seismic damage scenarios are a key tool for supporting the decision-making process, the preparedness, and for designing appropriate emergency responses. This paper provides the outcomes of a work consisting in improving the seismic risk assessment as a part of disaster risk governance and exposes the scientific background of this workflow. It illustrates its use with two earthquakes. Related post-seismic surveys provide observations that are useful to check the validity of the reference dataset. The paper also discusses the main characteristics of the rapid loss assessment tool that has been developed to provide operational information for crisis management.